Selection of a traffic management scheme at an intersection taking into consideration the traffic flow composition - Postranskyy, Taras; Boikiv, Mykola; Afonin, Maksym; Rogalskyi, Roman (Eastern-European Journal of Enterprise Technologies, 2020)
Traffic flows in large cities have a non-uniformed character of origin and changes. The main parameters are often sensitive to the changes in the environmental conditions, specifically, the time of the day, season, etc. The magnitudes that characterize traffic flows have a stochastic nature and therefore they are difficult to predict. According to this, indicators such as intensity, density and traffic speed over time and space are uneven. Taking this into consideration, during the development of traffic management schemes, there arises a necessity to take into consideration additional factors which are of probabilistic nature. This approach provides more opportunities in the traffic management process and makes it possible to use appropriate ways to choose traffic management methods in certain cases. This process involves detailed studies of traffic indicators. The approaches and methods for studying the main indicators of traffic flows were given. They include both field methods and simulation, which involves accounting of mathematical and physical patterns of traffic flows. It also makes it possible to predict the situation when choosing a traffic management scheme with the use of computer equipment. The results of the studies, which were conducted according to the described methods, were analyzed. These results indicate a close relationship between the relative traffic composition for the types of vehicles and the indicators of queuing and delays within the intersections. According to the results, mathematical dependences characterizing this relationship were obtained. It was established that the choice of a road traffic scheme at intersections should be made taking into consideration the traffic flow composition, as each regulation type is effective for a particular case